Lafcadio Hearn's America : ethnographic sketches and editorials - Hearn, Lafcadio, 1850-1904.; Bronner, Simon J. (Lexington, Ky. : University Press of Kentucky, 2002)
The American essays of renowned writer Lafcadio Hearn (1850-1904) artistically chronicle the robust urban life of Cincinnati and New Orleans. Hearn is one of the few chroniclers of urban American life in the nineteenth century, and much of this material has not been widely available since the 1950s. Lafcadio Hearn's America collects Hearn's stories of vagabonds, river people, mystics, criminals, and some of the earliest accounts available of black and ethnic urban folklife in America. He was a frequently consulted expert on America during his years in Japan, and these editorials reflect on th.
pt. 1. Communities and the "under side" of America. 1. Levee life : haunts and pastimes of the roustabouts -- 2. Saint Malo : a lacrustine village in Louisiana -- 3. Sicilians in New Orleans -- 4. The last of the New Orleans fencing-masters -- 5. A gypsy camp -- 6. Some pictures of poverty : impressions of a round with an overseer of the poor -- 7. Pariah people : outcast life by night in the East End -- 8. Les chiffonniers : how they live, work and have their being -- 9. Within the bars : how prisoners look, live, and conduct themselves -- 10. Cincinnati salamanders : a confederation of twenty little communities -- 11. Steeple climbers -- pt. 2. "Enormous and lurid facts" : language, folklife, and culture. 12. Cheek -- 13. The Creole patois -- 14. The Creole doctor -- 15. The last of the voudoos -- 16. New Orleans superstitions -- 17. The music of the masses -- 18. Black varieties : the minstrels of the row -- 19. Among the spirits : an Enquirer reporter communicates with his father -- 20. Some strange experience : the reminiscences of a ghost-seer -- 21. Haceldama : Hebrew slaughterers, gentile butchers, and consumptive blood-drinkers -- 22. The manufacture of yellow and Rockingham ware in Cincinnati -- pt. 3. Opinions of America. 23. Growth of population in America -- 24. The Labour problem in America -- 25. The race-problem in America -- 26. Some Japanese ideas of American policy -- 27. Prevention of cruelty to women -- 28. Recent American novels -- 29. American magazines -- 30. American art tastes -- 31. The French in Louisiana -- 32. The roar of a great city.
Includes bibliographical references (pages 231-233).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Hearn, Lafcadio, -- 1850-1904 -- Homes and haunts -- Anecdotes; Hearn, Lafcadio, -- 1850-1904 -- Political and social views; Hearn, Lafcadio, -- 1850-1904; United States -- Description and travel -- Anecdotes; United States -- Social life and customs -- 1865-1918 -- Anecdotes; United States -- Social conditions -- 1865-1918 -- Anecdotes; Ethnology -- United States -- History -- 19th century -- Anecdotes; Social classes -- United States -- History -- 19th century -- Anecdotes; États-Unis -- Mœurs et coutumes -- 1865-1918 -- Anecdotes; États-Unis -- Conditions sociales -- 1865-1918 -- Anecdotes; Ethnologie -- États-Unis -- Histoire -- 19e siècle -- Anecdotes; Classes sociales -- États-Unis -- Histoire -- 19e siècle -- Anecdotes; LITERARY COLLECTIONS -- Essays; Ethnology; Homes; Manners and customs; Political and social views; Social classes; Social conditions; Travel; United States; 1800-1918; Anecdotes; History